Effect of edible coating of sago starch-gelatine incorporated with papaya seed extract on the storage stability of Malaysian fish sausage (keropok lekor) - Bakar, Jamilah; Abdul Kadir, N. S.; Ahmad Mazlan, A. S.; Mohammad Rashedi, Ismail Fitry (Universiti Putra Malaysia Press, 2020)
The quality change of fish sausage (keropok lekor) coated in sago starch-gelatine coating with papaya seed extract (PSE) during chill storage (7°C) was determined. During storage, pH, thiobarbituric acid value (TBA), colour, moisture, and the total plate count were evaluated. pH of samples significantly dropped (p < 0.05) during storage, and the highest decrease was in control sample. The moisture content in control sample had an increasing trend while that of samples with 5 and 7% PSE coatings significantly decreased, and only a slight change for samples with 0% PSE coating. All samples had significant increase in their TBA values during storage. The presence of the coating provided a positive effect on the colour of the fish sausages since no significant colour changes were observed during storage. TPC of control and coated sausage in 0, 5, and 7% PSE exceeded the recommended microbial standard after 2, 6, 8, and 4 d of storage, respectively. Overall, coating with 5% of PSE was the most effective in retarding the quality deterioration of the fish sausages.